POTENSI ANAK USIA DINI MELALUI PENGEMBANGAN ASESMEN PENDIDIKAN KARAKTER - Palupi, Yulia (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Children are generation that determines a nation’s future. Children’s characters formed from now on will determine the nation’s character in the future. Children’s characters will be formed well if in their development process they get sufficient chance to express themselves freely. Character education is taken important to be started in childhood as it is an educational process aimed to develop values, attitude and behavior which reflect good morality. Positive values which are supposed to be owned based on character teaching are being pious, trustworthy, anticipative, positive-thinking, hard-working, civilized, dare to do right, dare to take risk, discipline, sincere, kind-hearted, godly, grateful, constructive, enthusiastic, initiative, responsible, tolerant, smart, careful, dynamic, cooperative, creative, independent, self- controlled, respectful to time, patriotic, friendly, compassionate, respectful to others’ works, assertive, diligent, humble, patient, having spirit of togetherness, open-minded, and tough in any situation.